Child Vulnerabilities in Nigeria: What is the Nature of Our Work as Child Protection Social Workers? - Tracy B.E. Omorogiuwa (Mediterranean Journal of Social Sciences, 2023)
Terms like child abuse, child labour, street children, child trafficking, and child marriage underscore the vulnerability of children worldwide, and underpin the imperative of affording them holistic care. Such services must address the underlying factors that elevate their vulnerability as is consistent with the person-in-environment focus of social work. Given our historical commitments and top-notch values, the social work profession, more than any other, is most concerned with the well-being of children. Yet, not much is known of our professional action in Africa, a region near the pyramid's pinnacle in child rights violation. This article presents the findings of a qualitative study, involving five voluntary organizations, which explored the nature of social work services to vulnerable children. Drawing on a constructivist framework, semi-structured interviews were conducted to gather data in Lagos and Abuja, Nigeria, and the results were then thematically analyzed. Findings indicate that social work services for vulnerable children require strengthening, since it does not address the root causes that exacerbate their vulnerability. Suggestions for navigating these challenges are explored. Received: 2 November 2022 / Accepted: 30 December 2022 / Published: 5 January 2023